ChemInform Abstract: A New and Concise Way to Enamides by Fluoroalkanosulfonyl Fluoride Mediated Beckmann Rearrangement of α, β‐Unsaturated Ketoximes. Issue 18 (May 2015) - Yan, Zhaohua; Xu, Yun; Tian, Weisheng
Abstract This mild and operationally simple method provides enamides in moderate yields.